Transforming TVET with AI: Economic Benefits of Technological Innovation in Education - Abdullah, Muhammad Irsyad; Hajamydeen, Asif Iqbal; Md Johar , Md Gapar (Online Journal for TVET Practitioners, 2025)
TVET is indispensable for building up the skilled human capital which is vital for the competitiveness of the economy and enhancing social cohesion. This systematic review focuses on the adoption of AI in TVET to assess its potential to revolutionize the sector and contribute to economic development. The research includes identification of the key academic databases containing articles and papers relevant to the AI in TVET, and emphasis on the recent publications. This is in line with the key findings highlighted above in sections on; Personalisation in learning. Administrative automation in institutions, AI and Industry needs at TAFE Queensland and Nanyang Polytechnic institutions. The review finds that AI in TVET positively impacts employment prospects, alleviates costs, and fosters innovations, implying that coordinated partnerships and policies should be pursued to optimise the AI benefits and contribute to sustainable economic development.